STRATEGI PENCEGAHAN STUNTING DI MASA PERIODE EMAS (GOLDEN PERIODE) MELALUI PERAN DASA WISMA DAN TOKOH AGAMA DI KELURAHAN LEKOBALO KOTA GORONTALO - Mohamad Anas Anasiru; Indra Domili; Magdalena Tompunu; Pepi S Umar (Bajang Institute, 2024)
The current health problem in Indonesia is stunting. Stunting or often called stunting or shortness, is a condition of failure to grow in aged children under five years (toddlers) due to chronic malnutrition and recurrent infections especially in the First 1,000 Days of Life (HPK), namely from fetus to child 23 months. Stunting originates from health problems and nutritional status of pre-pregnant, pregnant and pregnant women The breastfeeding period will determine the growth of the fetus and toddler. Pregnant mother Nutritional and health problems will put you at risk of giving birth to a low birth weight baby be a risk factor for stunting. Assistance for pregnant women and mothers who have Children aged 2 years are expected to be able to prevent and overcome stunting during this period 1000 HPK. The role of the community by involving the village community and religious leaders (mosque imams and recitation teachers) is considered quite important for increasing knowledge about Exclusive breastfeeding in preventing stunting